A rare case of tuberculous prostatitis / Nurul Yaqeen Esa …[et al.] - Esa, Nurul Yaqeen (Faculty of Medicine, 2016)
Tuberculous prostatitis is an uncommon form of tuberculosis infection. It is commonly seen in immunocompromised patients and in those of middle or advanced age. The diagnosis is often not straight forward due to the nature of its presentation. We report a case of tuberculous prostatitis in a young, healthy and immunocompetent patient, who initially presented with respiratory features, followed by episodes of seizures and testicular swelling. He was finally diagnosed with tuberculous prostatitis after prostatic biopsy. This case illustrates that in a high TB prevalence environment, when symptoms warrant, there should be a high clinical suspicion coupled with a thorough approach in order to arrive at a correct diagnosis of TB prostatitis.